Evaluation of Student Satisfaction in Using Academic Information System Services: A Structural Equation Modeling Approach - Abubakar, Ardiansyah; Arifin; Hasyim, Ahmad; Lestari, Sri Dian (Jurnal MSA (Matematika dan Statistika serta Aplikasinya), 2025)
The Academic Information System (SIAKAD) serves a pivotal function in enhancing both operational efficiency and the quality of academic services within higher education institutions, particularly amidst the accelerating shift toward digitalization in the education sector. Despite its strategic importance, the effectiveness of SIAKAD implementation is contingent upon the level of user satisfaction—most notably that of students—which remains insufficiently explored through analytical models capable of capturing intricate causal relationships. This study seeks to empirically examine the determinants of student satisfaction in utilizing SIAKAD by investigating the influence of system quality, information quality, and ease of use, with perceived usefulness positioned as a mediating construct. The research adopts the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, which is methodologically appropriate for complex models involving latent variables and non-normally distributed data. The analysis is based on survey data collected from 128 active undergraduate students at Universitas Patompo. The empirical findings indicate that information quality exerts a significant direct influence on student satisfaction (β = 0.547; p < 0.001) and an additional indirect effect mediated by perceived usefulness (β = 0.268; p < 0.001). Conversely, system quality and ease of use demonstrate no statistically significant effects. The coefficient of determination values (R² = 0.706 for satisfaction; R² = 0.615 for perceived usefulness) reflect a strong predictive capability of the model. These results affirm that information quality is the most salient predictor of user satisfaction, underscoring the imperative to prioritize content enhancement as a strategic direction in the advancement of academic information systems within the higher education landscape.